Lean management and innovation in operational efficiency: the EGR project implemented by Pirelli Tyre Brazil in Santo André plant - Prudentino, Vincenzo (2012)
This thesis aims to analytically describe and assess the implementation of lean manufacturing practices by Pirelli Tyre within its Latin American Industrial complex. In addition to a structured and vast description of Toyota production principles and lean thinking theoretical foundations, a special emphasis will be devoted to the EGR project (Especialistas em Gestão da Rotina), as a strategic tool to be used by the Italian multinational company in the upcoming future, so to achieve a more effective and efficient results in daily routine management. This project, representing a significant component of Pirelli Manufacturing System (PMS) and primarily geared to plant supervisors and coordinators, mainly consists of helping the firm to develop the corporate ability to correctly evaluate the potential gap existing between actual and expected results, in order to both understand deviations as well as underlying causes, and continuously improve company performance through process standardization and waste reduction. Those goals can be pursued by acting on two essential means: technical skills and behavioral leadership to support each project team; enhanced effectiveness in managing performance indicators across the different factory units, in accordance to KPIs set at the Head Quarter level. Furthermore, the research will be focused on the peculiar experience of Santo André plant, where EGR has firstly kicked off, with the aim to capture the relevant changes (on the organizational and economic side) brought to the company, through the conduction of field research and interviews, which are oriented to gather evidence, considerations and insights from all the organizational actors involved.